2019
DOI: 10.1039/c9cc04266k
|View full text |Cite
|
Sign up to set email alerts
|

π Complexes of P^P and P^N chelated gold(i)

Abstract: Tricoordinate gold(i) π-complexes containing P-based chelating ligands (P^P and P^N) were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“… 19 In our previous study, MeDalphos gold( i ) chloride was shown to catalyze the hydroarylation of styrene to give indoles 13a,b and the role of the gold( i ) π-complex as key intermediate was supported. 10 Here, π-systems with distinct electronic properties, MA and NPM as electron-poor alkenes and DHP as electron-rich alkene, were tested ( Scheme 3 ). 11 In all cases, the hydroarylation reaction proceeded and complete selectivity for C3-alkylation of the indole was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 In our previous study, MeDalphos gold( i ) chloride was shown to catalyze the hydroarylation of styrene to give indoles 13a,b and the role of the gold( i ) π-complex as key intermediate was supported. 10 Here, π-systems with distinct electronic properties, MA and NPM as electron-poor alkenes and DHP as electron-rich alkene, were tested ( Scheme 3 ). 11 In all cases, the hydroarylation reaction proceeded and complete selectivity for C3-alkylation of the indole was observed.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the role of the ancillary ligand on the ability of gold(I) to form stable p-complexes with a variety of alkenes, we then turned to the P^P chelating o-carboranyl diphosphine ligand for which a stable styrene complex (8) analogous to the P^N complex 1 was previously prepared. 10 The (P^P)AuCl precursor was reacted with AgSbF 6 in the presence of an excess of ethylene (9), DHP (10), MA (11) and NPM (12) in dichloromethane (Scheme 2). 11 The coordination of ethylene to the [(P^P)Au + ] fragment was readily established thanks to 1 H NMR spectroscopy: a new singlet appeared at 4.47 ppm, close to that found for the corresponding P^N ethylene complex 3 (4.10 ppm).…”
Section: Synthesis and Characterization Of (P^p)au(i) P-complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Rex1, a series of additional (autosomal) pluripotency factors have been found to repress XCI either directly or via controlling Xist regulators, such as Tsix or Rnf12 (Figure 5a). [22][23][24][102][103][104][105][106][107] By activating Tsix or repressing Xist, they could in principle also modulate the activation threshold of the proposed Tsix-mediated positive feedback loop. [16] Given their dynamical regulation during the onset of XCI and the fact that also autosomal activators control Xist, it might however be challenging to sense autosomal ploidy via pluripotency factor levels.…”
Section: Integration Of Autosomal Ploidy: Autosomal Regulators Countementioning
confidence: 99%
“…An alternate explanation is that electron rich alkenes facilitate displacement of ethylene from 1 to give a new p-complex in advance of oxidative addition. At atmospheric pressure, 19 F NMR profiling of the formation of (E)-3 d revealed the rapid disappearance of 1 (d F = À127.2 ppm) to give an intermediate (d F = À121.8 ppm) en route to the product; this intermediate is most likely the Au-p-complex of (E)-2 d. [14] When 1 was exposed to tert-butyl vinyl iodide (E)-2 g under analogous conditions, a similar intermediate formed, albeit to a lesser extent, indicating that displacement of ethylene still occurred, even though conversion to (E)-3 g was not observed. Overall, these observations indicate that oxidative addition, rather than displacement of ethylene from 1, is the more demanding step and that the alkenyl iodide must have the correct properties to facilitate this.…”
mentioning
confidence: 97%